Pola Perubahan Interaksi Agama Pada Ponpes Darul Umul (Teori Max Weber) - Sindiatus Soleha; Sugeng Harianto (CV. SINAR HOWUHOWU, 2026)
Social change in religious life is a phenomenon that continues to develop along with changes in social environments, technological advancements, and the dynamics of human interaction. Islamic boarding schools (pesantren) as Islamic educational institutions play an important role in shaping religious values, norms, and social behavior, yet they cannot be separated from the influence of changing times. This article aims to analyze the pattern of religious interaction changes at Darul Ulum Islamic Boarding School through Max Weber’s theory of social action. This study employs a library research method by examining various scientific sources, including journals, books, and previous studies related to social change, religious interaction, Islamic boarding schools, and social action theory. The findings indicate that changes in religious interactions within pesantren are influenced by internal and external factors, such as technological development, changes in communication patterns, social environmental influences, and the adaptation process of students toward emerging values. From Max Weber’s perspective, changes in students’ behavior and social interactions can be understood as forms of social action containing subjective meanings, both oriented toward religious values and influenced by rational considerations in responding to social changes. This study concludes that changes in religious interactions within pesantren not only reflect shifts in social behavior but also represent an adaptation process between traditional pesantren values and the development of modern society.